2008
DOI: 10.1142/s179329200800143x
|View full text |Cite
|
Sign up to set email alerts
|

C60(OH)n-ASSISTED DISPERSION OF SINGLE-WALLED CARBON NANOTUBES

Abstract: We demonstrate that C 60( OH )n-assists the dispersion of SWNTs in aqueous and nonaqueous solutions, which effectively exfoliates large-diameter SWNTs. The SWNT dispersions are characterized by absorption and photoluminescence spectra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Dispersion of SWNTs in an aqueous and nonaqueous solution using amphiphilic C 60 derivatives was also achieved ( Figure 14.3) [34]. Actually, C 60 (OH) n is soluble in an aqueous alkaline solution and isopropyl alcohol (IPA).…”
Section: Dispersion Of Swnts Using C 60 Derivativesmentioning
confidence: 94%
“…Dispersion of SWNTs in an aqueous and nonaqueous solution using amphiphilic C 60 derivatives was also achieved ( Figure 14.3) [34]. Actually, C 60 (OH) n is soluble in an aqueous alkaline solution and isopropyl alcohol (IPA).…”
Section: Dispersion Of Swnts Using C 60 Derivativesmentioning
confidence: 94%
“…Various types of dispersant reagents have been investigated, including surfactants, p-conjugated compounds, amine, and polymers. It was reported that chiral-index-selective dispersion and PL wavelength shifts [8][9][10][11][12][13] occur depending on the solvents and dispersant reagents; therefore, the dispersion conditions are important for chiral index assignment and for evaluating the proportions of the different chiral SWCNTs in a mixture.…”
Section: Introductionmentioning
confidence: 99%